(untitled) (Journal of Economic Research & Business Administration, 2016)
A new look at human resource management, and taking into account the potential of employees of the organization becomes more important right now. Modern business is characterized by the increasing pace of change, globalization, advances in information and communication technologies, innovation in production and services sectors. The market is constantly changing, dictates new requirements. In a highly competitive global fundamental solution is the joint efforts of the company and its employees initiative. Employees – the most important asset of the organization, which is to be preserved, developed and used for competitive success. In order to respond to today’s business requirements, you need to develop a humane working environment. Human capacity, the ability to put the head of the right target and effectively dispose of resources are the main factor of success of the organization. In the article the basic problems of management of human resources quality. Substantiates the modern requirements to the quality of human resources.